The Arcadian friends inventing the English landscape garden - Richardson, Tim (Bantam Press, 2008)
Between the 1680s and the 1750s, a group of politicians and poets, farmers and businessmen, heiresses and landowners began to experiment with the phenomenon that was to become the English landscape garden. Arguably the greatest British art form ever invented, these gardens were built to charm and delight, to shock and inspire all who visited. That these gardens, including Castle Howard, Stowe, Painshill and Rousham, are still so popular with visitors today is a testament to the innovation and passion of this extraordinary group of eccentrics and visionaries. The Arcadian Friends introduces us to a period of political and personal intrigue, where fantastic biblical landscapes competed for space with temples to sexual freedom; and where the installation of a water feature was a political act. Tim Richardson's highly engaging and illuminating perspective on the politics and culture of England during the Enlightenment is required reading for the legions of fans of the great gardens of England.
Keywords: Geschichte 1700-1800; Geschichte 1715-1750; Geschichte; Gardens -- Great Britain -- History -- 18th century; Landscape gardening -- Great Britain -- History -- 18th century; Landschaftsgarten; Großbritannien